2011
DOI: 10.1080/01919512.2011.602006
|View full text |Cite
|
Sign up to set email alerts
|

Some Ozone Applications in Seafood

Abstract: The use of ozonized seawater to reduce and eliminate bacterial pathogens in mariculture facilities and to extend shelf life of marine food products is demonstrated. Consequent benefits of this treatment are also discussed. Laboratory and pilot experiments were conducted using ozone gas to reduce disease-producing Vibrio sp. bacteria at a shrimp (Litopenaeus vannameii) hatchery in Ecuador, South America. Pacific Ocean seawater was treated in a 1,540 L capacity fiberglass contact tower (5-7 min retention) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Ozone treatments oxidize various cellular components leading to membrane leakage and eventually cell death ( Figure 1 ), it has high biocidal activity, requires short contact times, and can take place at the aquaculture level or on the final product. As an example of the former, applying 0.07 mg/L of ozone directly to seawater at shrimp hatcheries has been shown to allow the survival of shrimp, but eliminate pathogenic vibrios ( Blogoslawski and Stewart, 2011 ). Studies on seafood spoilage are generally assessed based on several metrics including bacterial levels (CFU/g), the levels of gases produced from seafood breakdown such as total volatile basic nitrogen (TVB-N), trimethylamine nitrogen (TMA-N), total volatile acid (TVA), and ranking the food on fit-for-consumption scales based on sight and smell ( Ordóñez et al, 2000 ; Arkoudelos et al, 2007 ; Pantazi et al, 2008 ).…”
Section: Ozone Treatmentmentioning
confidence: 99%
“…Ozone treatments oxidize various cellular components leading to membrane leakage and eventually cell death ( Figure 1 ), it has high biocidal activity, requires short contact times, and can take place at the aquaculture level or on the final product. As an example of the former, applying 0.07 mg/L of ozone directly to seawater at shrimp hatcheries has been shown to allow the survival of shrimp, but eliminate pathogenic vibrios ( Blogoslawski and Stewart, 2011 ). Studies on seafood spoilage are generally assessed based on several metrics including bacterial levels (CFU/g), the levels of gases produced from seafood breakdown such as total volatile basic nitrogen (TVB-N), trimethylamine nitrogen (TMA-N), total volatile acid (TVA), and ranking the food on fit-for-consumption scales based on sight and smell ( Ordóñez et al, 2000 ; Arkoudelos et al, 2007 ; Pantazi et al, 2008 ).…”
Section: Ozone Treatmentmentioning
confidence: 99%
“…found that compared with flake ice, the counts of aerobic mesophiles, psychrotrophic bacteria, Enterobacteriaceae and proteolytic microorganisms in megrim muscle with ozonized slurry ice treatment for 14 days significantly decreased, which highlighted the antibacterial effect of ozone. Meanwhile, ozone is maintained in the sealed ice and released slowly with the melting of ice during storage and transportation, which can improve the problem of the instability of ozone preservation 22 …”
Section: Introductionmentioning
confidence: 99%
“…The interaction of molecular diatomic oxygen (O 2 ) to an oxygen atom gives rise to ozone (O 3 ), which is a highly unstable triatomic oxygen molecule (De Mendonça Silva & Gonçalves, ). Ozone has been employed as an oxidizing agent in water treatment and in the food industry and is considered a powerful sanitizer (Blogoslawski & Stewart, ; Gonçalves, ). In recent years, ozonification has attracted more interest for use in fish preservation due to its ability to reduce spoilage organisms (Glatman, Sachs, Khanin, Drabkin, & Gelman, ; Pastoriza, Bernardez, Sampedro, Cabo, & Herrera, ).…”
Section: Ozonificationmentioning
confidence: 99%